Implementation of Social Studies Using Local Wisdom to Inform Learning as an Attempt to Strengthen Resilient Character in Elementary Students - Murfiah, Uum; Maman, Maman; Ayuningtyas, Tyagita (Universitas Pendidikan Indonesia, 2024)
This research investigates how social studies instruction based on local knowledge helps primary school pupils develop resilient character. Many primary school pupils participated in this research as respondents, which used a quantitative methodology. A questionnaire instrument to gauge students' knowledge of local wisdom and how Local wisdom-based learning impacts the development of resilient traits like self-reliance, self-discipline, and responsibility was used to gather data. Local wisdom-based social studies instruction and students' development of resilient character were shown to be strongly correlated. This study demonstrates how important it is to include local knowledge into the curriculum, particularly in social studies classes, to effectively train a generation to meet global issues without losing their cultural identity. This study makes a unique contribution by creating a character-based education paradigm based on resilient attitudes like self-control, bravery, diligence, and never giving up. Thus, the findings of this research may be used as a basis for creating educational policies that are more culturally appropriate and inclusive.